A Mixed Integer Linear Programming (MILP) Model for Optimal Design of Water Network - Zainatul Bahiyah , Handani (2011)
This work presents the development of a new systematic technique to target fresh water consumption and wastewater generation for systems involving multiple contaminants when all options of water minimization including source elimination, reduction, reuse/recycle, outsourcing and regeneration are considered simultaneously. This problem is formulated as mixed integer linear programming (MILP) and implemented in Generalized Algebraic Modeling System (GAMS). The consideration of process changes will lead to optimal design of minimum water utilization network. The MILP model proposed in this work can be used to simultaneously generate the minimum water targets and design the minimum water network for global water-using operations for buildings and industry. The approach is illustrated by using an industrial involving a chlor-alkali plant. Significant water savings for the industrial case study is achieved, illustrating the effectiveness of the proposed approach.